TI-RICH GABBRO OF FEDORIVKA APATITE-ILMENITE DEPOSIT - MYTROKHYN, O.; MYTROKHINA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The ores of Fedorivka deposit occuring in a Ti-rich olivine gabbro intrusion within Volodarsk-Volynsky massif of Korosten complex have been investigated. It has been established that mineral composition of the ore gabbro is typical for basic rocks of anorthosite-rapakivi granite association. Distinctive features are intermediate plagioclases An41-47, ferrous olivines Fa46-52 and augites Wo36-40 En30-35 Fs26-32 as so as high contents of ilmenites, Ti-magnetites and apatites. It has been determined a rythmic changing of TiO2, Fe2O3, V₂O, MnO and Cr₂O3, contents in the coexiting ilmenites and magnetites depending on depth. The average weighted chemical chem composition Fedorivka intrusion corresponds to subalkaline olivine ferrobasalt enriched in Ti and P. Geology, mineralogy and petrography of Fedorivka intrusion allow to refer it to layered basic intrusion with genetic relation to Proterozoic massif type anorthosites.